Information Needs among Parents of Cancer Children: A Systematic Review - Nurhidayah, Ikeu; Nani Nurhaeni; Isna Hanifah; Allenidekania Allenidekania (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: When a child is diagnosed with cancer, parents are affected, especially if they are unprepared and do not understand the illness. Parents' informational needs are frequently expressed and vary, so identifying parent needs is critical before providing health or nursing interventions. Aims: This review aimed to identify the information needs of parents of children with cancer. Method: PubMed, Medline, and CINAHL were applied to conduct electronic searches. The terms "information needs”, "parent”, "cancer”, and "child” were combined using Boolean expressions "OR” and "AND”. The inclusion criteria were non-experimental studies published in English within the last 10 years (2011-2021). A risk of bias assessment was conducted for each included study using the Joanna Bridge Institute critical appraisal tools. After identification and screening, the articles were filtered according to the criteria with a total of 15 articles included in this study. Furthermore, data extraction and synthesis were carried out. Narrative synthesis is used by collecting information on the findings of the article to be grouped into themes of finding problems. Results: Four themes emerged based on the results of the analysis: types of information needed; information formats; provision of information; and sources of information. Conclusion: This study concluded that parents require accurate information that addresses their specific information needs and is appropriate for their child's cancer stage. The provision of balanced written and verbal information, as well as information that is complete, accurate, and reliable, makes it easier for parents to increase their knowledge about caring for their children.